Factors influencing the yield of mesenteric angiography in lower gastrointestinal bleed - Rasuli, Pasteur (Baishideng Publishing Group Inc, 2014)
AIM: To assess if certain triaging rules could be established to optimize the yield of mesenteric angiography. METHODS: Medical records of 101 patients were retrospectively reviewed and parameters relating to age, gender, pulse rate, blood pressure, serum hemoglobin, intensive care unit (ICU) admission, and the number of packed red blood cells (PRBC) transfused in the 12 and 24 h prior to the angiography were tabulated in two groups with positive and negative angiography results. RESULTS: We found no correlation between gender, pulse rate, blood pressure or serum hemoglobin and positivity of the mesenteric angiogram. But patients with positive angiogram were found to be on average 7 years older (73.2 years vs 65.9 years old) (P = 0.02). Angiogram was positive in 39.3 % (11/28) of patients admitted in ICU vs 23.2% (17/73) who were admitted elsewhere in the hospital (P = 0.03). In the 12 and 24 h prior to angiography, patients with a positive angiogram received a mean of 2.7 ± 2.3 and 3.3 ± 2.6 units of PRBC s respectively, while patients with a negative angiogram had a mean of 1.6 ± 1.9 (P = 0.02) and 2.1 ± 2.6 units (P = 0.04) received respectively in the same period. CONCLUSION: Older age, ICU admission, having received at least 4 units PRBC over 12 h or 5 units over 24 h prior to angiogram are leading indicators for a positive study.